MPC and FOC for LVRT performance in hybrid renewable energy systems - Oday Saad Fares; Riyadh G. Omar; Kassim A. Al-Anbarri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
This paper proposes a wind and solar energy-based hybrid generation system integrated with a photovoltaic (PV) array controlled using model predictive control (MPC) and a doubly fed induction generator (DFIG) wind turbine controlled using field-oriented control (FOC). The system employs cascaded-based and bridge-based structures for two renewable sources, and they are connected to an ordinary common load, and designed to meet the stringent conditions of low-voltage ride-through (LVRT) required during fault conditions and grid-side perturbations. In order to safeguard the power electronic converter from sharp voltage dips, a crowbar protection circuit is used on the rotor side of the DFIG. In order to verify the enhanced LVRT capability of the offered system, extensive modeling, control design, implementation steps, and numerous simulation results have been included. The use of sophisticated control methodologies and protective measures improves the reliability and stability of wind-solar power plants. Simulation results reveal that for a serious grid disturbance, the system manages to maintain the output voltage at 70% of its nominal value and keeps the waveform steady and sinusoidal. In addition, the control scheme ensures that the rotor current is not just sinusoidal but also well-balanced, yielding a steady-state electromagnetic torque. This combination of control and protective measures is paramount for achieving stability, power quality, and reliability in current hybrid renewable power systems.